Legislative responses to environmental degradation in geomorphologically sensitive areas: Integrating legal frameworks, scientific validation, and governance approaches - Rami Salih; Ibrahim Khilel Khinger; Shaker Jameel Sajat Awadh; Majid Fadhil Ziboon; Ali Alsaray (Environment and Social Psychology, 2025)
Environmental degradation refers to the depreciation and wearing down of the physical and natural resources leading to irreversible damage to the state of the environment in geomorphologically sensitive areas, and acts as a common challenge, and a point of intersection of both physical vulnerability and legislation inadequacy. This study therefore examines how legislative responses; enforcement mechanisms and community engagement interact with geomorphic features to create degradation patterns across five stratified sites. A multi-method approach is employed that incorporates field erosion measurement, geotechnical analysis of slope stability and legislative performance metrics including compliance rates, inspection frequency and spatial congruence of legal protections. This study presents advanced indices, the Legal-Geomorphic Coupling Index and the Regulatory Adaptability Score to measure how legislative structural and spatial effectiveness relate to environmental issues. Furthermore, distributed surveys are used to translate stakeholder perception into quantifiable measures such as governance legitimacy and public trust. Found that regions where the legal and geomorphic systems aligned more closely, where development was better able to adapt to regulatory demands, and where community trust was present experienced less erosion even under challenging topographical conditions. Conversely, sites with weak enforcement and spatially disconnected legal boundaries exhibit elevated degradation even in the face of nominal legal protections. Drawing on post-heroic construction of science and nature, the study argues for an integration of scientific data into legislative planning and urges adaptive, spatially intelligent legal systems. Moreover, it underlines that institutional trust and participatory governance are vital for successful, sustainable environmental policies in vulnerable landscapes. The study provides methodological tools and policy recommendations to help shape more effective, responsive and ecologically sound environmental governance. These results highlight both methodological contributions and practical policy implications for scaling legislation across diverse regions, including case applications in Europe, Asia, and Latin America.